2008
DOI: 10.1007/s10561-008-9109-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cryopreservation or heating on the mechanical properties and histomorphology of rat bone-patellar tendon-bone

Abstract: The effects of cryopreservation on tendon allograft have been reported, but remain unclear, particularly the potential effects on mechanical properties and histological changes by ice crystal formation. There are also few studies about effects of heating for sterilization of tendon. We evaluated the effect of cryopreservation or heating on the mechanical properties and histomorphology of rat bone-patellar tendon-bones (BTBs). BTBs were processed by cryopreservation at -80 degrees C for 3 weeks, or heating at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…Fresh specimens were pre-fixed with 0.1 M cacodylate buffer containing 4% paraformaldehyde and 2.5% glutaraldehyde, and then post-fixed with 2% osmium tetraoxide in 0.1 M cacodylate buffer and embedded in Quetol 651 resin (Nissin EM Corp., Tokyo, Japan) according to the manufacturer’s instructions. In addition, to evaluate the structure of bone cells in the frozen state, bones were fixed using a freeze-substitution method, as previously described (Park et al 2009). Briefly, bones were first transferred to acetone containing 2% osmium tetroxide (OsO 4 ) cooled at −80°C, and then stored at −80°C for 1 week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh specimens were pre-fixed with 0.1 M cacodylate buffer containing 4% paraformaldehyde and 2.5% glutaraldehyde, and then post-fixed with 2% osmium tetraoxide in 0.1 M cacodylate buffer and embedded in Quetol 651 resin (Nissin EM Corp., Tokyo, Japan) according to the manufacturer’s instructions. In addition, to evaluate the structure of bone cells in the frozen state, bones were fixed using a freeze-substitution method, as previously described (Park et al 2009). Briefly, bones were first transferred to acetone containing 2% osmium tetroxide (OsO 4 ) cooled at −80°C, and then stored at −80°C for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore hypothesized that repeated freeze–thaw cycles would reduce the number of surviving cells in allografts, and potentially represents a simple method for reducing immunogenicity. Although we previously reported that a single freeze–thaw cycle did not affect the mechanical properties of tendons (Park et al 2009), it is unclear how repeated freeze–thaw treatments would affect tendon mechanics and function.…”
Section: Introductionmentioning
confidence: 91%
“…In other field, there are many studies showing that the biomechanical behavior of tissue collagen framework, is not altered by effect of cryopreservation / thaw cycle, in vascular (Armentano, 2006;Bia, 2006;Langerak, 2001Langerak, , 2007Pukacki, 2000), tendon , (Woo, 1986;Park, 2009) or bone tissues. (Hamer, 1996).…”
Section: The Interaction Between Ecm Components and The Physic-chemimentioning
confidence: 99%
“…As radiografias foram avaliadas quanto a doença óssea ou nutricional, fraturas da crista da tíbia, sinais de artroplastia ou osteotomia da tuberosidade da tíbia. Após remoção de tecidos moles estas foram armazenadas em freezer convencional, com temperatura de -20° Celsius (PARK et al, 2009;GOH et al, 2010;JUNG et al, 2011). As peças foram armazenadas em embalagens plásticas com dimensões de 50 centímetros de altura e 30 centímetros de largura.…”
Section: Limitações Do Estudounclassified
“…(JUNG et al, 2011). Esta temperatura foi baseada em estudos similares previamente realizados (DENNLER et al, 2006;KOWALESKY;LINS et al, 2009;PARK et al, 2009;ETCHEPAREBORDE et al, 2010;GOH et al, 2010;BUTLER et al, 2011;JUNG et al, 2011 DOVERSPIKE et al, 1993;DUPUIS et al, 1994;CHAUVET et al, 1996;BONFIM;PACCOLA, 2000;INNES et al, 2000;MORRIS;LIPOWITZ, 2001;BOUDRIEAU, 2005;CONZEMIUS et al, 2005;DAMUR, 2005;HOFFMANN et al, 2006;BARAÚNA et al, 2007;TARTARUNAS et al, 2007;STEINS;SCHMOEKEL, 2008;VOSS, et al, 2008;GUERRERO et al, 2009;DYMOND;GOLDSMID;SIMPSON, 2010;BISGARD et al, 2011;KEMPER et al, 2011;STEINBERG et al, 2011). Entretanto é sabido que a avaliação biomecânica pode trazer informações importantes para estudos clínicos futuros.…”
Section: Dispositivo Para Corpo De Provaunclassified